Health Professionals' Opinions About Secondary Prevention of Diabetes-Related Foot Disease. Issue 5 (October 2022) - Drovandi, Aaron; Seng, Leonard; Crowley, Benjamin; Fernando, Malindu E.; Evans, Rebecca; Golledge, Jonathan
Purpose: The purpose of this study was to explore the perceptions of health professionals regarding the ideal design of a remotely delivered diabetes-related foot disease (DFD) secondary prevention program. Methods: A qualitative study involving 33 semistructured phone interviews was conducted with health professionals with experience managing DFD. Interviews discussed the role of health professionals in managing DFD, their experience in using telehealth, perceived management priorities, preferences for a secondary prevention management program, and perceived barriers and facilitators for such a program. Interviews were audio-recorded and transcribed, and inductive thematic analysis was used to derive key themes. Results: Three themes were derived: (1) barriers in current model of DFD care, (2) facilitators and ideas for a remotely delivered secondary prevention program, and (3) potential challenges in implementation. DFD care remains acute-care focused, with variability in access to care and a lack of "clinical ownership." Patients were perceived as often having poor knowledge and competing priorities, meaning engagement in self-care remains poor. Participants felt a remote secondary prevention program should be simple to follow and individualized to patients' context, with embedded support from a case manager and local multidisciplinary service providers. Challenges to implementation included limited DFD awareness, poor patient motivation, patient-related issues with accessing and using technology, and the inability to accurately assess and treat the foot over telehealth. Conclusions: Health professionals felt that an ideal remotely delivered secondary prevention program should be tailored to patients' needs with embedded support from a case manager and complemented with multidisciplinary collaboration with local service providers.